Formasi Spiritual Jemaat Lansia dengan Paradigma yang Holistik dan Intergenerasional - Grace Emilia (Veritas : Jurnal Teologi dan Pelayanan, 2022)
Spiritual formation in a Christian context is a continuous life-long process for a Christian to grow and imitate Christ. This process does not merely occur cognitively and individualistically but holistically and communally, and it also applies to senior adults (65 years and above). However, due to historical influences, many churches are still doing a fragmented and segregative spiritual formation. As a result, senior adult parishioners might not grow maximally and tend to be passive and isolated onlookers who merely become ministry targets of the younger ones. There needs to be a paradigm change for the senior adults to keep growing and functioning in the community as part of their spiritual formation. This article proposes the significance of spiritual formation for senior adults with a more holistic and intergenerational paradigm which utilizes a qualitative method, including a literature review. According to this study, senior adult parishioners should be served by following God’s design on human nature and through the perspective of ministering-with-senior adults instead of ministering-to-senior adults. This article thus aims to inspire churches to apply and develop the spiritual formation of senior adult parishioners through the holistic and intergenerational paradigm, not fragmented and segregative as it used to be.